2019
DOI: 10.5964/psyct.v12i2.356
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary aspects of a new eating disorder: Orthorexia nervosa in the 21st century

Abstract: In this theoretical study, certain characteristics of orthorexia nervosa (ON) are assessed. As a type of disordered eating, ON is characterized as pathological healthy eating obsession. By reviewing previous literature, four orthorexic traits are investigated whether they meet the conditions of becoming adaptive drivers of human behavior. First, learned neophobia to avoid “improper” foods is considered as an advantageous strategy, secondly, ON being a cohesive force based on common beliefs and its religious, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…From an evolutionary perspective, Bóna et al [ 91 ] found that some of the orthorexic traits meet the conditions of becoming adaptive drivers of human behavior, whereas others show non-adaptive health behavior tendencies. Indeed, orthorexia may be conceptualized as complex eating behaviors that include pathological and non-pathological health dimensions [ 37 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…From an evolutionary perspective, Bóna et al [ 91 ] found that some of the orthorexic traits meet the conditions of becoming adaptive drivers of human behavior, whereas others show non-adaptive health behavior tendencies. Indeed, orthorexia may be conceptualized as complex eating behaviors that include pathological and non-pathological health dimensions [ 37 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, ON may be considered as adaptive due to selective healthy eating and its social characteristics (orthorexic behaviours are relevant evolutionary strategies because they can enable earning recognition and honours from others [11]). Therefore, ON may be viewed (tentatively) as a healthy diet protecting one's health but also as a phenomenon having negative influence on health [12], however, this viewpoint should be adopted with some caution, due to the limited number of available studies on these subjects, and should hence be further tested in the future studies.…”
Section: Introductionmentioning
confidence: 99%
“…(Alvarenga et al 2012). Furthermore, 51.8% of regular exercisers (Almeida et al 2018) and 27.7% of athletes (Bona et al 2019) reported ON symptoms.…”
Section: Introductionmentioning
confidence: 97%